The MPA/MPP in the Anglo-democracies: Australia, Canada, New Zealand, the United Kingdom, and the United States. Issue 4 (1st December 2016) - Pal, Leslie A.; Clark, Ian D.
Abstract: Should one expect convergence among MPA/MPP programs around the world, and in particularly among programs in the "Anglo-sphere" or among the Anglo-democracies, defined here as Australia, New Zealand, Canada, the United Kingdom, and the United States. For reasons of shared history and language, one might expect convergence, but there are counter-arguments as well that note, for example, the rich diversity among American programs alone. The paper analyzes 99 programs drawn from among these countries to find an answer. The analysis is wider in scope and more granular than anything that has been done to date, with data that allow comparisons of: (1) subject matter emphasis between policy and management, (2) the amount of required quantitative content, and (3) program length (number of standardized courses required to graduate). After illustrating a standardized metric of comparison we show that the convergence hypothesis cannot be sustained. Our conclusion entertains several conjectures about why this might be the case.